Kandungan Logam Cr, Cu, dan Zn pada Daging Siput Sedut (Cerithidea montagnei) dengan Ukuran Berbeda di Perairan Pulau Kundur Kabupaten Karimun Provinsi Kepulauan Riau - Surya, Mujibur Rahman; Amin, Bintal; Yoswati, Dessy (Jurnal Perikanan dan Kelautan, 2018)
This research was conducted in October 2017 by taking samples from Tanjung Berlian and Gading Sari coastal waters of Kundur Island, Karimun Regency, Kepulauan Riau Province. This study aims to analyze the heavy metal content of Cu, Cr and Zn on C. Montagnei, to analyze the relationship of heavy metal content with snail size, to evaluate the level of pollution status of Kundur Island waters and to estimate the safety level of snail consumption by human. The metal content on the small size of the snail is larger than the larger size. The average content of Cu in Station 1 was found in small size (1.3877 μg/g), medium size (1,0783 μg/g) and large size (1.6100 μg/g), whilst in Station 2 was found as follow: large size with an average of 1.4417 μg/g. Cr content in Station 1 for small size (5.0383 μg/g), medium size (1.4850 μg/g) and large size (3.0950 μg/g). Snail in Station 2 was only found at Station 2 (1.9517 μg/g). Zn content in small size of snail was in Station 1 (117,4500 μg/g), medium size (122,5200 μg/g) and large size (115,9200 μg/g). Meanwhile, Zn content in snail at Station 2 was 104.7283 μg/g in large size.